KADAR VITAMIN C DAN TINGKAT KESUKAAN PRODUK BUAH POTONG SEGAR SELAMA MASA PAJANG - Gustika Damanik, Anita; Suryawan Wiranatha, A.A.P. Agung (Agrotekno; Vol. 14, No. 1 Februari 2008, 2012)
The objective of this research were to know the content of vitamin C, and the consumer preferences on several combination of fresh cutting fruits that were packed in several types of packaging during shelve life. This research was undertaken by factorial experiment using randomized block design. There were three factors in this research namely: (i) combination of fruits (water melon and rock melon; water melon and papaya; rock melon and papaya); (ii) types of packaging used (without packaging; mika; stretch film); and (iii) duration of shelve life (10 hours; 20 hours; 30 hours). Analysis was undertaken on vitamin C contents, and organoleptic test on several parameters namely colour, aroma, texture, taste, and overall acceptance. The research result showed that the combination of fruits, types of packaging and duration of shelve life were significantly affecting the vitamin C content. The most stable of vitamin C content was found in the fruits combination of water melon and papaya which was packaged by using stretch film within 10 hours. The highest overall acceptance was found in the fruits combination of water melon and rock melon which was packaged by using mika within 10 hours of shelve life.
Keywords: fruits varieties, packaging types, shelves life